A taxonomical revision of Ilex (Aquifoliaceae) in the Pan-Himalaya and unraveling its distribution patterns - Hong, De-Yuan (Phytotaxa, 2015)
All relevant specimens of the genus Ilex in 11 major herbaria: B, BM, CDBI, E, K, KUN, P, PE, SZ, W, WU, in addition to A (types), were critically examined. Field observations were conducted in E Himalaya (Bomi, Mêdog, and Zayü of Tibet) and the Hengduan Mountains (Tengchong, Yunnan). As a result of this taxonomic revision, 14 species and 12 varieties are reduced to synonyms and one species is reduced to a subspecies; one species, I. shweliensis, is restored with reservation; one new species, I. gansuensis, is described from SE Gansu, while records of five species supposedly present in the Pan-Himalaya are found to be due to misidentification or mislocation by previous authors. Thus 41 species are recognized in the Pan-Himalaya, not 60 species as reported in the literature. A key to these 41 species is presented. The types of six names are designated here. In addition, noteworthy disjunct distribution patterns are shown for four species.